Adult education, spirit and the 'New Age': Sir George Trevelyan and the Shropshire Adult Education College (SAEC) at Attingham 1948-76 - Clancy, Sharon. L. (2017)
This thesis presents an interdisciplinary study of post-Second World War short-term residential adult education, through an investigation of the Shropshire Adult Education College (SAEC), 1948-1976. This was located at Attingham Park, Atcham, Shropshire, now a National Trust property. George Lowthian Trevelyan, its Warden until 1971, was both an educational pioneer and a charismatic New Age leader. The study, conducted with support from the National Trust, examines the importance of memory, place and space and utilises oral history and archival materials to uncover and re-present the story of one college as a lens on a form of adult education which has enduring relevance. The investigation is informed by class-based, political and cultural perspectives. Since the College’s demise little had been done to evaluate this important experimental period of adult education. This study involved a slow uncovering process, akin to restoration. Although some more robust infrastructural ‘markers’ of the College, such as student-made stained glass windows and some mosaics, remain in situ, others, like the ceiling paintings of night sky constellations, have been erased or removed. For many of the former staff, students and academic tutors interviewed, this ‘painting over’ is a metaphorical deletion of a period of history important to them as individuals, and – as the closing down of a space of post-war reconstruction, creative thinking and renewal – socially significant. Many students and staff found their experiences transformational. Early courses, reflecting Trevelyan’s view of citizenship within a “classless” post-war democracy, embraced an eclectic and diverse range of largely local students. He was, however, an innovator and experimenter: along with literature, music and crafts, architecture and conservation, the curriculum evolved, reflecting and articulating his particular vision of cosmological, spiritual and ecological unity. This utopian thinking spoke of the dangers of rampant materialism and destruction of the earth, but was intertwined with a romantic desire to conserve a British way of life overseen by the hereditary aristocracy. An anthroposophical message, based on Rudolf Steiner’s arcane and esoteric teachings, was central. As the ‘New Age’ became Trevelyan’s focus, divisions emerged between his acolytes and those hostile to the changes – including residential and area-based tutors responsible for mainstream courses, governors and students. Students and tutors on ‘esoteric’ courses were increasingly people with privileged backgrounds, drawn from Trevelyan’s own national network. This led to charges of elitism. Ultimately, though arguably a post-hoc rationalisation, this has been seen as key to the decision to close the College.